Towards a Decent Labour Market for Low-Waged Migrant Workers - Lange, Tesseltje de; Rijken, Conny; Project Muse; Project Muse. (Project Muse, 2020)
Central to this edited volume is the legal position and the labour situation of non-EU and EU low-waged migrant workers. Towards a Decent Labour Market for Low-Waged Migrant Workers presents ground breaking research on policies and practices in search of striking a right balance between the economic ambitions and the negative consequences thereof, for labour market dynamics such as down-ward wage pressures, unfair competition, the abuse of migrant workers and even the long-term setback for the children of previously low-waged migrant workers. Imbalances or presumed imbalances between free market mechanisms, labour migration policies, labour market protection and corrective mechanisms to protect migrant workers, thus come to the fore. The contributors to this volume will deconstruct some of these imbalances, and shed light on its causes, consequences and interrelatedness with other factors. Possible solutions that contribute to a decent labour market, in which rights of low-waged migrant workers are more respected, will be discussed.
Towards a decent labour market for low-waged migrant workers : an introduction / Tesseltje de Lange and Conny Rijken -- The challenge of migration : politics as labour and labour as politics / Bert van Roermund -- How 'low-skilled' migrant workers are made : border-drawing in migration policy / Regine Paul -- From competing to aligned narratives on posted and other mobile workers within the EU? / Mijke Houwerzijl and Annette Schrauwen -- Labour arbitrage on European labour markets : free movement and the role of intermediaries / Jan Cremers and Ronald Dekker -- The seasonal workers directive : another vicious circle? / Margarite Helena Zoeteweij -- Towards protection of vulnerable labour migrants in Sweden : the case of the Thai berry pickers / Petra Herzfeld Olsson -- Asylum seekers' limited right to work in the Netherlands / Tesseltje de Lange -- When bad labour conditions become exploitation : lessons learnt from the Chowdury case / Conny Rijken -- Employer sanctions : instrument of labour market regulation, migration control, and worker protection? / Lisa Berntsen and Tesseltje de Lange -- Bottom-up approaches to the regularisation of undocumented migrants : the Swiss case / Lucia Della Torre -- When nationalism meets soft skills : towards a comprehensive framework for explaining ethno-migrant inequality in the Dutch labour market / Hans Siebers -- Collective agreements and equal opportunities for women and disadvantaged groups / Johan Graafland.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Labor market -- European Union countries; Migrant labor -- European Union countries; Foreign workers -- European Union countries; Electronic books; Electronic books